Projecting and Transforming the Net Structure of Delivery Chains in Conditions of Latest Geo-Political Changes - Yu. I. Yaroslavceva (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Logistics in Russia has been actively developing lately. One of key trends in this process implies building a net structure by logistic companies as a foundation for efficient and competitive delivery chains. The article studied development of a net structure of delivery chains and specific features of new reality of net functioning, where their transformation shall take place. It was found out that strategic goals, which are targeted at by logistic company plans are based on rational net configuration. Availability of rationally projected logistic chains both inside the country and abroad became unquestionable competitive advantage that allowed companies to move goods to the final consumer. Globalization of economy in certain countries and the development of international trade in the last decade provided logistic companies with wide opportunities for profitable territorial location of delivery chain links. However, the desired success of logistic companies in attaining goals of functioning faced today’s transport and logistics reality caused by pressure of numerous factors connected with sanctions against Russia, which led to the necessity to transform net configuration. In view of this the authors discussed in more detail the mechanism of some factors, which can result in distortion of product flows and arising of new ones, including in international delivery chains.